PENDEKATAN EDUKATIF GURU BIMBINGAN KONSELING DALAM MENANGANI SISWA BERMASALAH DI SMP MARIA ASSUMPTA KLATEN - Hanifah Widayanti (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
This study aims to provide an in-depth description of the implementation of the educational approach by Guidance and Counseling (GC) teachers in addressing behavioral problems among students at SMP Maria Assumpta Klaten. The background of this research stems from the need to replace traditional punitive methods, which often have negative impacts on students’ psychological development and character formation. As an alternative, the educational approach is considered more effective because it emphasizes the development of self-awareness, responsibility, and behavioral change through learning and reflection processes. This study employs a descriptive qualitative method with the main subjects being GC teachers and several students who have received counseling services through the educational approach. Data were collected through in-depth interviews, direct observations, and document analysis of counseling records. The findings reveal that the educational approach emphasizing the use of positive and logical consequences—encourages students to understand the meaning behind their actions and take responsibility for their behavior. Students who previously exhibited deviant behavior showed noticeable improvement in discipline, self-awareness, and reflective thinking. Therefore, the educational approach proves to be an effective, constructive, and humanistic strategy for character development among students. The study recommends that this approach be implemented consistently and integrated into the overall guidance and counseling services in schools.